A review of the trends in the first six years of a palliative care unit in Trinidad and Tobago - Karen Cox; Stacey Chamely; Astra Chang; Sandhya Maharaj; Isioma Isitor; Raisa Abdullah (Caribbean Medical Journal, 2023)
Objectives: To present key data accumulated from the first six years of a publicly funded Palliative Care Unit (PCU) in Trinidad and Tobago. Methods: This was an observational, descriptive, retrospective study. Data was sampled from five (5) service areas: admissions to the PCU, out-patient clinic, hospital consultations, family meetings and telephone calls. Demographic data, reason for referral, diagnosis, time to consultation and outcome data were collected. Results: The Palliative Care Unit was accessed by 2579 patients between 2014 - 2020. Ages ranged from 3-103 years. There were 1004 unique in-patient admissions, most of whom fell in the age range 62-82 years. 83% had a documented cancer diagnosis. 90% of patients spent less than 30 days at the PCU. Discharge rate was 25%. Most out-patient clinic referrals were for symptom management - 90.8% of these had cancer. Median time from palliative care review at out-patient clinic to death was 34 days (Interquartile range (IQR) 12-107 days). For the hospital consultation service, 82.8% had a cancer diagnosis. Median time from palliative care review to death was 11 days, Interquartile range (IQR) 4-39 days. Conclusion: The Caura PCU meets the needs of a small proportion of palliative patients in Trinidad and Tobago. The service is accessed mostly by patients with cancer, and referrals are frequently made late in the disease trajectory. This service needs to be expanded to include a community/home-based service and a paediatric service. Palliative care needs to become integrated throughout the health service in Trinidad and Tobago.